Forging a Laboring Race : The African American Worker in the Progressive Imagination - Lawrie, Paul R. D. (Book collections on Project MUSE., 2017)
For many thinkers across the colour line, the 'negro problem' was inextricably linked to the concurrent 'labour problem, ' occasioning debates regarding blacks' role in the nation's industrial past, present and future. This volume charts the history of an idea-race management-building on recent work in African American, labour and disability history to analyse how ideas of race, work, and the 'fit' or 'unfit' body informed the political economy of early 20th century industrial America.